Ten‐Gram‐Scale Facile Synthesis of Organogadolinium Complex Nanoparticles for Tumor Diagnosis. Issue 11 (24th February 2020) - Wei, Zhenni; Jiang, Zhenqi; Pan, Chunshu; Xia, Jianbi; Xu, Kaiwei; Xue, Ting; Yuan, Bo; Akakuru, Ozioma Udochukwu; Zhu, Chengjie; Zhang, Guilong; Mao, Zheng; Qiu, Xiaozhong; et al.
Abstract: The market of available contrast agents for clinical magnetic resonance imaging (MRI) has been dominated by gadolinium (Gd) chelates based T 1 contrast agents for decades. However, there are growing concerns about their safety because they are retained in the body and are nephrotoxic, which necessitated a warning by the U.S. Food and Drug Administration against the use of such contrast agents. To ameliorate these problems, it is necessary to improve the MRI efficiency of such contrast agents to allow the administration of much reduced dosages. In this study, a ten‐gram‐scale facile method is developed to synthesize organogadolinium complex nanoparticles (i.e., reductive bovine serum albumin stabilized Gd‐salicylate nanoparticles, GdSalNPs‐rBSA) with high r 1 value of 19.51 mm −1 s −1 and very low r 2 / r 1 ratio of 1.21 ( B 0 = 1.5 T) for high‐contrast T 1 ‐weighted MRI of tumors. The GdSalNPs‐rBSA nanoparticles possess more advantages including low synthesis cost (≈0.54 USD per g), long in vivo circulation time ( t 1/2 = 6.13 h), almost no Gd 3+ release, and excellent biosafety. Moreover, the GdSalNPs‐rBSA nanoparticles demonstrate excellent in vivo MRI contrast enhancement (signal‐to‐noise ratio (ΔSNR) ≈ 220%) for tumor diagnosis. Abstract : A ten‐gram‐scale facile method is developed to synthesize organogadolinium complex nanoparticles (i.e., reductive bovine serum albumin stabilized Gd‐salicylate nanoparticles, GdSalNPs‐rBSA) with high r 1 value of 19.51 mm −1 s −1 and very low r 2 / r 1 ratio of 1.21 ( B 0 = 1.5 T) for high‐contrast T 1 ‐weighted MRI of tumors.